Synthesis of Binuclear Isoquinoline‐ and Pyridine‐Fused Benzimidazole‐4, 7‐diones by Magnetic MOF‐199‐Catalyzed C–C Coupling/Cyclization Followed by Oxidation. Issue 25 (17th June 2019) - Diep, Thi Duyen; Dao, Pham Duy Quang; Cho, Chan Sik
Abstract : 2‐(2‐bromoaryl)‐4, 7‐dimethoxy‐1 H ‐benzo[ d ]imidazoles and ( Z )‐2‐(2‐bromovinyl)‐4, 7‐dimethoxy‐1 H ‐benzo[ d ]imidazoles react with 1, 3‐diketones by microwave irradiation in DMF in the presence of a catalytic amount of recyclable Fe3 O4 @SiO2 @MOF‐199 along with a base to give binuclear isoquinoline‐ and pyridine‐fused benzimidazoles, respectively. Treatment of such binuclear N‐fused hybrid scaffolds with ceric ammonium nitrate in acetonitrile/H2 O or HBr/FeCl3 in H2 O affords binuclear isoquinoline‐ and pyridine‐fused benzimidazole‐4, 7‐diones in good to high yields. Abstract : A new synthetic method of binuclear isoquinoline‐ and pyridine‐fused benzimidazole‐4, 7‐diones via a recyclable copper‐catalyzed coupling and cyclization followed by oxidation has been developed.